The effect of FIFA 11+ kids warm-up program on agility in football: An experimental study - Khoiril Anam; Anies Setiowati; Nanang Indardi; Fajar Awang Irawan; Eva Ayu Aditia; Aziz Amrulloh; Nugroho Susanto; Özgür Eken; Hendra Setyawan; Zhanneta Kozina; Ratko Pavlović (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Injury is one of the problems that often occurs in young football players. The players are encouraged to carry out the FIFA 11+ Kids, a warm-up program to minimize injuries for football players. This study aims to determine the effect of this program on young football players’ agility. This research was an experimental study with a pretest and posttest control group design. Using a purposive sampling technique, the research selected 20 football school students as the research sample. The samples were 11-12 years old. To collect data, the research used the Illinois agility test, aiming to measure the level of agility. The data were then administered using the Wilcoxon test with a significant p-value <5%. This study found a significant difference between the results of speed measurements before and after being given the FIFA 11+ Kids warm-up treatment. In the treatment group, the average pretest result was 19.03±0.74, with a score range of 17.50-20 seconds. Meanwhile, the average posttest result was 18.28±0.84, with a score range of 16.75-19.78 seconds. The p-value was 0.005 (p<5%). This study concludes that the FIFA 11+ Kids program can improve the agility of young football players. Despite the promising results, this research suggests further investigation to add research samples from various demographic characteristics.